Feature Recognition System for Rotational Features - Tan, CheeFai; Ismail, N.; Ranjit, S.S.S. (Asian Network for Scientific Information, 2013)
This paper presents the development of a knowledge-based features recognition system for mechanical parts. The main aim of the research is to concentrate on recognition of rotational features, namely, blind hole, through hole and slanting hole to be used in automatic process planning system. The rule-based technique applied to recognise rotational features. The recognition criteria are based upon geometrical data from STandard for Exchange of Product data file (STEP) of computer-aided design (CAD) system. The system consists of several modules, namely, pre-processing module, inference engine module and user interface module. The developed system succeed the design activities in manufacturing industries.